Archaeological excavations in Durkadi Nala : an early palaeolithic pebble-tool workshop in Central India - Armand, Jorge, 1940- (Munshiram Manoharlal Publishers, 1983)
Report on the excavation at the ancient Narbada River, West Nimad District, Madhya Pradesh.